2020
DOI: 10.1016/j.matt.2020.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Highly Ordered and Dense Thermally Conductive Graphitic Films from a Graphene Oxide/Reduced Graphene Oxide Mixture

Abstract: A new approach to make graphitic thin films from graphene oxide (G-O) is presented. By incorporating small-diameter, reduced GO platelets with GO , graphitized films show improved density and crystalline order when compared with pure GO. Mechanical pressing of the graphitized films increased density but decreased crystallinity. A subsequent high-temperature heat treatment improved atomic order beyond that seen before mechanical pressing. In-plane thermal conductivity is on par with highly oriented pyrolytic gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 29 publications
2
57
0
Order By: Relevance
“…This is probably because the extra GO sheets disrupted the polymer matrices, causing the GO sheets to change from systematic orientations to random orientation, and therefore, the reduction in conductivity, a phenomenon has been observed in other studies as well. [ 67,68 ] Meanwhile, it was noticed that the brittle SAN 250 has better conductive performance compared to the rubbery counterpart at the same GO‐loading content. This may be due to the more uniform distribution of GO in the brittle polymer matrix; however, the detailed reasons should be explored in future studies.…”
Section: Resultsmentioning
confidence: 99%
“…This is probably because the extra GO sheets disrupted the polymer matrices, causing the GO sheets to change from systematic orientations to random orientation, and therefore, the reduction in conductivity, a phenomenon has been observed in other studies as well. [ 67,68 ] Meanwhile, it was noticed that the brittle SAN 250 has better conductive performance compared to the rubbery counterpart at the same GO‐loading content. This may be due to the more uniform distribution of GO in the brittle polymer matrix; however, the detailed reasons should be explored in future studies.…”
Section: Resultsmentioning
confidence: 99%
“…With the rapid development of graphene and graphene-based materials throughout the world, some new methods, new processes and new technologies [21,22,[24][25][26][27], such as molecular welding, molecular assembling, flow coating and centrifugal casting, as shown in Figures 6b and 8, have been increasingly developed to fabricate graphene-based graphite films with high thermal conductivity for thermal management application. This will surely provide some reference for the preparation strategy of PI-derived graphite films.…”
Section: New Fabrication Technologymentioning
confidence: 99%
“…In addition, little attention has been paid to the alignment of graphene nanosheets or platelets when designing the interfacial interactions. Recently, some reports [11][12][13][14] have demonstrated significant enhancement in the mechanical and electrical properties of graphene films by simply decreasing the wrinkling of graphene nanosheets and thus improving their alignment. Additionally, it has been reported that some crosslinkers can not only provide strong interfacial interactions between adjacent graphene platelets but also improve the alignment of graphene platelets, resulting in remarkable mechanical and electrical properties.…”
Section: Progress and Potentialmentioning
confidence: 99%
“…Based on recent results, 5,[9][10][11][12][13][14] two consistently ignored issues need to be recognized when assembling graphene nanosheets into macroscopic graphene films. Graphene films are usually thought to be composed by alternating a one-layer graphene nanosheet and one-layer crosslinker.…”
Section: Introductionmentioning
confidence: 99%